Use of molecular markers in bean crop improvement - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2010)
Molecular markers are Specific fragments of DNA that can be identified within the whole genome. In a genetic cross the characteristic of interest will stay linked with the molecular markers allowing for selection. Markers have the advantage of speeding up the selection process since analysis can be done at any developmental stage. Their neutrality also makes them useful in genetic diversity studies and they allow the introgression of particularly difficult traits.